2020
DOI: 10.5334/ijc.977
|View full text |Cite
|
Sign up to set email alerts
|

Regeneration of Underused Natural Resources by Collaboration Between Urban and Rural Residents: A Case Study in Fujiwara District, Japan

Abstract: Whereas the underuse of resources due to the tragedy of anticommons is well known, resource underuse due to demand loss has received little attention. In this paper, I examined the governance to regenerate underused natural resources by a case study on semi-natural grassland, called "Uenohara," in Fujiwara District located in a Japanese mountain village. Uenohara served as local commons, providing roofs, fertilizer, forage, and food to local residents until the 1950s. However, changes in social conditions abol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Although Hirahara (2020) has shown that social factors have vital roles in the new governance of natural resource management [10], this study illustrates each causal relationship from the cultural services perspective. However, one of the limitations of this study is that the subject of analysis is just one form of forest recreation in a certain area.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Although Hirahara (2020) has shown that social factors have vital roles in the new governance of natural resource management [10], this study illustrates each causal relationship from the cultural services perspective. However, one of the limitations of this study is that the subject of analysis is just one form of forest recreation in a certain area.…”
Section: Discussionmentioning
confidence: 82%
“…About 10 core members of FCS plan forest recreation and call on the general participants to join activities. This study focuses on this case because their activities address the modern issue of regenerating underused natural resources, and a previous study [10] clarified the details of governance of natural resource management.…”
Section: Outlinesmentioning
confidence: 99%
See 2 more Smart Citations
“…As seen in many industrialized countries (Berge and Mckean 2015), most of Japan's rural communities have been abandoning their management of their common property forests. Previous scholarship has emphasized socio-economic causes, such as the sinking economic value of timber, the energy revolution, and population decline (Shimada 2014;Miyanaga and Shimada 2018;Hirahara 2020). However, through a microdata analysis of the 2000 census, this paper demonstrates how legal and institutional factors also cause difficulties in forest use and management.…”
Section: Introductionmentioning
confidence: 99%